AN IN-DEPTH COMPARATIVE ANALYSIS OF THE LEXICO-SEMANTIC STRUCTURES OF LEGAL TERMS IN ENGLISH AND UZBEK WITH A FOCUS ON CONCEPTUAL MAPPING, TERMINOLOGICAL EQUIVALENCE, AND JURIDICAL CONTEXTUALIZATION - Khujakulov Sunnatullo (Western European Studies, 2025)
This study offers a comparative analysis of the lexico-semantic structures of legal terms in English and Uzbek, focusing on conceptual mapping, terminological equivalence, and juridical contextualization. It investigates how legal concepts are linguistically constructed in both languages and examines the alignment or divergence in meaning and legal function. Using frameworks from legal linguistics, cognitive semantics, and translation studies, the research identifies three types of equivalence: one-to-one, one-to-many, and non-equivalence. Case studies demonstrate the challenges posed by the structural differences between the AngloAmerican common law and Uzbek civil law systems. The study emphasizes the need to contextualize legal terms within their respective legal frameworks and explores morphological, semantic, and historical factors, including Russian and international legal influences on Uzbek legal terminology. It also addresses the complexities of translation when direct equivalence is unavailable, proposing strategies for achieving functional and descriptive equivalence. The conclusion underscores the need for enhanced bilingual legal dictionaries, targeted translator training, and the development of legal ontologies to bridge conceptual gaps. This research is valuable for legal translators, linguists, comparative lawyers, and policymakers, offering insights into the interplay of language, law, and culture while proposing practical methods for improving semantic interoperability in legal discourse
Keywords: Lexicosemantics; equivalence; translation; terminology